2014
DOI: 10.1111/jomf.12080
|View full text |Cite
|
Sign up to set email alerts
|

Does Family Instability Make Girls Fat? Gender Differences Between Instability and Weight

Abstract: Data from the 1979 National Longitudinal Survey of Youth and the Young

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 91 publications
1
20
0
Order By: Relevance
“…Maternal height and weight were directly assessed and used to calculate maternal BMI (Centers for Disease Control and Prevention, ). A continuous maternal BMI measurement was included to control for the intergenerational transmission of weight status (Crossman, Sullivan, & Benin, ; Gibson et al., ; Hernandez, Pressler, Dorius, & Mitchell, ).…”
Section: Methodsmentioning
confidence: 99%
“…Maternal height and weight were directly assessed and used to calculate maternal BMI (Centers for Disease Control and Prevention, ). A continuous maternal BMI measurement was included to control for the intergenerational transmission of weight status (Crossman, Sullivan, & Benin, ; Gibson et al., ; Hernandez, Pressler, Dorius, & Mitchell, ).…”
Section: Methodsmentioning
confidence: 99%
“…Any gender difference in stress and body mass may have its origins in childhood but evidence on gender differences in stress and weight gain in childhood is limited and unclear. For example, a few studies suggest that family stress, financial stress and peer problems experienced in childhood are more likely to lead to weight gain for girls than boys (Hernandez et al., 2014; Hernandez & Pressler, 2015; Vanaelst et al, 2014), yet childhood exposure to maternal risky health behaviors is more likely to promote boys’ weight gain than girls’ (Hernandez & Pressler, 2015). Moreover, potential gender differences in childhood stress effects that are not apparent by adolescence may emerge later in life although empirical evidence on this point is rare.…”
Section: Gender Differencementioning
confidence: 99%
“…A separate literature on childhood stress suggests that higher levels of childhood stress are associated with greater weight gain from childhood to adolescence (Gundersen et al, 2011; Shankardass et al, 2014; Stenhammar et al, 2010; Wells et al, 2010), with limited and mixed evidence for gender differences in this association (see Hernandez et al, 2014; Hernandez & Pressler, 2015; Vanaelst et al, 2014). Previous studies have not considered whether stress trajectories that begin in childhood and fluctuate throughout adulthood are connected in ways that have long-term consequences for stability and change in body mass throughout the life course, or whether these processes unfold in different ways by gender (Gundersen et al, 2011).…”
mentioning
confidence: 99%
“…Another intervention found targeting co-parent relationships could also influence the parent-child relationship and child well-being outcomes. More specifically, Hernandez, Pressler, Dorius, and Mitchell (2014) found that family instability, including formations and dissolutions of parental partnerships in the home, put young girls at greater risk of being overweight or obese as young adults. These stressors to the family system may place these girls at higher risk of developing obesogenic food behaviors .…”
Section: Co-parentsmentioning
confidence: 99%
“…21 Specifically, co-parent relationship instability has been associated with increased obesity risk among young girls. 22 Thus, if a mother perceives misalignment with her co-parent in parenting decisions, this challenge in the co-parent relationship may also be associated with more frequent obesogenic behaviors in the home.…”
Section: Co-parent Influencesmentioning
confidence: 99%